In silico search of inhibitors of Streptococcus mutans for the control of dental plaque. (November 2017) - Ochoa, Rodrigo; Martínez-Pabón, María Cecilia; Arismendi-Echeverri, María Adelaida; Rendón-Osorio, Willer Leandro; Muskus-López, Carlos Enrique
Highlights: Potential genes of cariogenic species were proposed based on genome comparisons. S. mutans protein interaction network was rebuilt by related species orthologue. A list of 20 proteins related to virulence were identified. Phosphotransferase system and pyruvate kinase were prioritized for future analysis. 10 compounds with predicted affinity to pyruvate kinase were identified by docking. Abstract: Biofilm is an extremely complex microbial community arranged in a matrix of polysaccharides and attached to a substrate. Its development is crucial in the pathophysiology of oral infections like dental caries, as well as in periodontal, pulp, and periapical diseases. Streptococcus mutans is one of the most effective microorganisms in lactic acid production of the dental biofilm. Identifying essential Streptococcus mutans proteins using bioinformatics methods helps to search for alternative therapies. To this end, the bacterial genomes of several Streptococcus mutans strains and representative strains of other cariogenic and non-cariogenic bacteria were analysed by identifying pathogenicity islands and alignments with other bacteria, and by detecting the exclusive genes of cariogenic species in comparison to the non-pathogenic ones. This study used tools for orthology prediction such as BLAST and OrthoMCL, as well as the server IslandViewer for the detection of pathogenicity islands. In addition, the potential interactome of Streptococcus mutans was rebuilt by comparing it to interologues of other species phylogenetically close to or associated with cariogenicity. This protocol yielded a final list of 20 proteins related to potentially virulent factors that can be used as therapeutic targets in future analyses. The EIIA and EIIC enzymatic subunits of the phosphotransferase system (PTS) were prioritized, as well as the pyruvate kinase enzyme, which are directly involved in the metabolism of carbohydrates and in obtaining the necessary energy for the microorganism's survival. These results will guide a subsequent experimental trial to develop new, safe, and effective molecules in the treatment of dental caries.